PENERAPAN REALISTIC MATHEMATICS EDUCATION (RME) DALAM ONLINE LEARNING UNTUK MEMBANTU PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII [THE IMPLEMENTATION OF REALISTIC MATHEMATICS EDUCATION (RME) IN ONLINE LEARNING TO HELP GRADE 8 STUDENTS UNDERSTAND MATHEMATICAL CONCEPTS] - Saragih, Theresia Ami Meigia; Tamba, Kimura Patar (JOHME: Journal of Holistic Mathematics Education, 2022)
Students' conceptual understanding in Indonesia is still low. In the school that the author observed, students in grade 8 have an average total conceptual understanding of 48% with sufficient criteria. The solution to overcome this problem is by implementing RME. The purpose of writing this paper is to describe the application of RME in helping students understand concepts using descpritive qualitative research methods.  The results of this study indicate that RME is applied in online learning in the following steps: first, providing and explaining contextual problems to be solved by students; second, students solve contextual problems for the development of mathematical models in their own way; third, discuss and compare any problem solving given by students; fourth, students conclude and summarize the concept of the topic being studied. The implementation of RME in online learning is carried out using a flipped classroom approach. In this reverse class approach, horizontal mathematics is done asynchronously while vertical mathematics is synchronous. Students' understanding of concepts after the implementation of RME has increased. In RME knowledge is acquired through horizontal and vertical mathematics, while interactivity in this approach helps students understand concepts.BAHASA INDONESIA ABSTRACT: Pemahaman konsep siswa di Indonesia tergolong masih rendah. Pada suatu sekolah yang diobservasi peneliti, siswa kelas VIII memiliki total rata-rata pemahaman konsep 48% berkriteria cukup. Untuk mengembangkan pemahaman konsep siswa, matematika tidak seharusnya diberikan secara siap saji kepada siswa. Oleh sebab itu solusi untuk mengatasi masalah ini adalah dengan penerapan Realistic Mathematics Education (RME). Tujuan penulisan paper ini yaitu mendeskripsikan penerapan RME dalam membantu pemahaman konsep siswa dengan metode penelitian kualitatif deskriptif. Hasil penelitian ini menunjukkan bahwa RME diterapkan dalam pembelajaran online dalam beberapa langkah berikut yaitu pertama, memberikan dan menjelaskan masalah kontekstual untuk diselesaikan oleh siswa; kedua, siswa menyelesaikan masalah kontekstual untuk pengembangan model matematika dengan cara masing-masing; ketiga, mendiskusikan dan membandingkan setiap penyelesaian masalah yang diberikan oleh siswa; keempat, siswa menyimpulkan dan merangkum konsep pembelajaran tersebut. Penerapan RME dalam pembelajaran online ini dilakukan dengan pendekatan kelas terbalik (flipped classroom). Pada pendekatan kelas terbalik ini, matematika horizontal dilakukan secara asinkronus sementara matematika vertikal secara sinkronus. Pemahaman konsep siswa setelah penerapan RME mengalami peningkatan. Dalam RME pengetahuan diperoleh melalui matematika horizontal dan vertikal, sementara interaktivitas dalam pendekatan ini membantu pemahaman konsep siswa.